Regimes of substrates processing and deposition nanofilms using the laser-plasma method - Goncharov, Victor K.; Puzyrev, Michail V.; Prakapenia, Dzmitry P.; Shulhan, Nikita I.; Stupakevich, Valery Yu. (Journal of the Belarusian State University. Physics, 2021)
The physical processes occurring in a laser-plasma source is used for deposition nanostructures. The laser-plasma source is an erosion laser plume of the target material and a substrate located in a vacuum chamber. It has been proposed to place a grid between the laser target and the substrate. A negative potential is applied to the grid relative to the laser target to smoothly adjust the parameters of the particles deposited on the substrate. As a result, a particles flow is formed after a grid. This particle flow is predominantly consisting of ions. The energy of the ions can be reliably and smoothly controlled by applying a positive potential to the grid relative to the substrate. It has been experimentally proved method for deposition of nanofilms using ion beams from the laser plasma. It has been shown that different regimes of substrate surface treatment can be implemented in the laser-plasma source for deposition nanostructures. Using this source, you can sequentially clean the surface of the substrate without depressurizing the vacuum chamber, and create a pseudodiffusion layer of the laser target material near the surface layer of the substrate. It will allow producing it possible to obtain highly adhesive nanofilms with predetermined parameters.